Kausa Penolakan Masyarakat Terhadap Peraturan Perundang-Undangan Bidang Hukum Keluarga - Musafir Abrar; Hasyim Aidid; Ardi Ardi; Misbahudin Misbahudin; Samsuddin Samsuddin (State Islamic University (UIN) of Sunan Ampel, 2022)
This paper discusses on how the reaction of Islamic society toward the issuance of law regulation about family law. As we know that this regulation is on the constitution No 1 Year 1974 about marriage. In this paper, the author tries to describe the points of reason, so that it arouses rejection toward the regulation. This explanation uses historical approach method, which we have to get back from the starting point of the regulation issuance and how the society's reaction toward this law regulation. The primary reason of why the society rejects some important points in the regulation is because they see that in the regulation there are articles and slauses that are against and even harmful of opposite to prevalling system in Islamic law. So does in discussing about the legislation, there are some opinions expecially for those who wants the legislation of such regulation can be applied to all of Indonesian society without offending their religions. However as the times evolve, legislating the regulation has essence to support the continuity of Islamic law within the society. The society is able to receive the regulation without reducing the existing limitations of Islamic system.